Penerapan Multimedia Presentasi (Powerpoint) berbantuan Zoom Meeting dalam Pembelajaran Ekonomi - Sri Nopembril Rozanti; Dina Ramadhanti (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
AbstrakPenelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar siswa yang mengikuti pembelajaran online pada mata pelajaran Ekonomi. Pemindahan ruang belajar di kelas ke kelas online membuat siswa mengalami masalah dalam pembelajaran mereka. Untuk mengatasi hal tersebut digunakan multimedia presentasi (powerpoint) berbantuan zoom meeting. Penelitian ini merupakan penelitian tindakan kelas yang melibatkan siswa kelas X IK2 MAN Koto Baru Solok. Hasil penelitian menunjukkan bahwa multimedia presentasi (power point) terbukti meningkatkan kualitas pembelajaran yang meliputi tindakan guru, tindakan siswa, aktivitas belajar siswa, dan hasil belajar siswa. Tindakan guru mengalami peningkatan dari 87,50% menjadi 97,50%. Meskipun tingkat keberhasilan tindakan guru pada Siklus I dan Siklus II sama-sama sangat berhasil, persentase keberhasilan tindakan tersebut mengalami peningkatan. Tindakan siswa juga mengalami peningkatan dari 58,33% menjadi 85,42%. Tingkat keberhasilan tindakan siswa meningkat dari berhasil menjadi sangat berhasil. Aktivitas belajar siswa mengalami peningkatan dari 52,06% menjadi 68,89%. Meskipun tingkat keberhasilan aktivitas belajar siswa pada Siklus II masih sama dengan Siklus I, yaitu berhasil, persentase keberhasilan aktivitas belajar siswa pada Siklus II mengalami peningkatan dibandingkan dengan Siklus I. Demikian juga dengan hasil belajar yang mengalami peningkatan dari rata 76,00 menjadi 83,97. Meskipun kemampuan siswa terhadap materi pelajaran Ekonomi yang diajarkan sama-sama berkualifikasi baik pada Siklus I dan Siklus II, semua siswa telah mencapai batas KKM. Pada prasiklus, hanya 10 orang siswa yang mencapai batas KKM, lalu pada Siklus I meningkat menjadi 18 orang. Selanjutnya, sebanyak 35 orang siswa pada Siklus II telah mencapai batas KKM. Dengan demikian, multimedia presentasi (power point) berbantuan aplikasi zoom meeting cloud dapat digunakan untuk mengatasi permasalahan dalam pembelalajaran jarak jauh secara online. khususnya pada Mata Pelajaran Ekonomi. Kata kunci: multimedia presentasi, powerpoint, zoom meeting, ekonomi AbstractThis study aims to improve the activities and learning outcomes of students who take online learning in Economics subjects. The transfer of classrooms from classrooms to online classes makes students experience problems in their learning. To overcome this, a multimedia presentation (powerpoint) with the help of a zoom meeting is used. This research is a classroom action research involving students of class X IK2 MAN Koto Baru Solok. The results showed that multimedia presentations (power point) were proven to improve the quality of learning which included teacher actions, student actions, student learning activities, and student learning outcomes. The teacher's actions have increased from 87.50% to 97.50%. Although the success rate of teacher actions in Cycle I and Cycle II were both very successful, the percentage of success of these actions increased. Student actions also increased from 58.33% to 85.42%. The success rate of student actions increased from successful to very successful. Student learning activities have increased from 52.06% to 68.89%. Although the success rate of student learning activities in Cycle II is still the same as Cycle I, which is successful, the percentage of success of student learning activities in Cycle II has increased compared to Cycle I. Likewise, learning outcomes have increased from an average of 76.00 to 83.97 . Although the students' ability to the Economics subject matter taught is equally qualified in Cycle I and Cycle II, all students have reached the KKM limit. In the pre-cycle, only 10 students reached the KKM limit, then in Cycle I it increased to 18 people. Furthermore, as many as 35 students in Cycle II have reached the KKM limit. Thus, multimedia presentations (PowerPoint) assisted by the Zoom meeting cloud application can be used to overcome problems in online distance learning. especially in Economics Subjects. Keywords: multimedia presentation, PowerPoint, zoom meeting, Economics subjects TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//